Riboflavin and ultraviolet light for pathogen reduction of murine cytomegalovirus in blood products. Issue 4 (1st December 2014) - Keil, Shawn D.; Saakadze, Natia; Bowen, Richard; Newman, James L.; Karatela, Sulaiman; Gordy, Paul; Marschner, Susanne; Roback, John; Hillyer, Christopher D.
<x xml:space="preserve">Abstract</x> Background Two studies were performed to test the effectiveness of riboflavin and ultraviolet (UV) light treatment (Mirasol PRT, Terumo BCT) against murine cytomegalovirus (MCMV). The first study utilized immune‐compromised mice to measure the reduction of cell‐free MCMV. A second study used a murine model to evaluate the ability of Mirasol PRT to prevent transfusion‐transmitted (TT)‐MCMV infection. Study Design and Methods Human plasma was inoculated with MCMV and then treated with Mirasol PRT. The viral titer was measured using an infectious dose 50% assay in nude mice. Mice were euthanized on Day 10 posttransfusion, and their spleens were tested for the presence of MCMV DNA using polymerase chain reaction (PCR). Mirasol PRT was also evaluated to determine its effectiveness in preventing TT‐MCMV in platelets (PLTs) stored in PLT additive solution. PLTs were inoculated with either cell‐associated MCMV or cell‐free MCMV and then treated with Mirasol PRT. Mice were transfused with treated or untreated product and were euthanized 14 days posttransfusion. Blood and spleens were assayed for MCMV DNA by real‐time‐PCR. Results Using nude mice to titer MCMV, a modest 2.1‐log reduction was observed in plasma products after Mirasol PRT treatment. TT‐MCMV was not observed in the mouse transfusion model when either cell‐free or cell‐associated MCMV was treated with Mirasol PRT; MCMV transmission was uniformly observed in mice transfused with untreated PLTs. Conclusions These results suggest that using riboflavin and UV light treatment may be able to reduce the occurrence of transmission of human CMV from infectious PLTs and plasma units.